Extended wear soft contact lenses induce corneal epithelial changes. Issue 12 (December 1994) - Tsubota, K; Toda, I; Fujishima, H; Yamada, M; Sugawara, T; Shimazaki, J
Abstract : The purpose of this study was to determine the corneal epithelial alterations induced by various types of contact lenses. By employing the specular microscope, the corneal epithelia of 60 patients who had worn contact lenses for more than 1 year were re-examined along with 15 myopic controls. The morphological changes in aphakic patients who changed from extended wear soft to extended wear rigid gas permeable lenses were also studied. The mean cell area of the corneal epithelium was 621.5 (SD 92.5) microns 2 for daily wear rigid gas permeable lenses (n = 15), 645.8 (98.1) microns 2 for daily wear soft lenses (n = 15), and 634.7 (88.6) microns 2 for extended wear rigid gas permeable lenses (n = 15), none of which differed significantly from the control value of 610.5 (98.1) microns 2. Only the extended wear soft lens group (n = 15) showed significantly enlarged epithelia (806.1 (50.1) microns 2, p < 0.01 versus the other groups). The epithelium partially returned to normal after changing from extended wear soft lenses to extended wear rigid gas permeable ones. The corneal epithelium showed increased cell area only with extended wear soft contact lenses which are known to pose a risk for corneal infection.